Unilateral enlargement of the lateral lingual tonsil: An immunohistochemical study and literature review - Almeida, Lana Kei Yamamoto; Silveira, Heitor Albergoni [UNESP]; Ferrisse, Tulio Morandin [UNESP]; Silva, Evânio Vilela [UNESP]; Almeida, Luciana Yamamoto [UNESP]; Bufalino, Andreia [UNESP]; León, Jorge Esquiche (Elsevier, 2020)
Besides the Waldeyer's ring, other lymphoid aggregates can also be detected in the soft palate, floor of the mouth and ventral tongue. The lingual tonsil is located at the base of the tongue and related to circumvallate papillae, whereas subepithelial lymphoid tissue at the posterior lateral portion of the tongue and related to foliate papillae constitutes the lateral lingual tonsil. Unilateral tonsillar enlargement is critical, because it can suggest malignancy, notably non-Hodgkin lymphoma or squamous cell carcinoma. Herein, we report an unusual presentation of unilateral enlargement of the lateral lingual tonsil, diagnosed as follicular lymphoid hyperplasia.
Keywords: Immunohistochemistry; Lateral lingual tonsil; Lingual tonsil; Tongue; Waldeyer's ring